Islamization: A Sociological Approach - Mohammad Musyfiqur Rahman (Indonesian Journal of Islamization Studies, 2024)
Islamisation: A Sociological Approach" intricately explores the processes of cultivating an Islamic society. It delves into the interplay between individual and systemic transformations, aligning with Islamic doctrines. The meticulous examination includes integrating Islamic principles into societal frameworks, exploring social psychology, human soul cognition, schema control, behavioral modifications, community dynamics, and emotional management. The discourse spans foundational Islamisation aspects to constructing persuasive models, emphasizing the need for narratives resonating across the Islamic realm. The treatise addresses fostering uniformity in Islamic governance, focusing on human motivation, informational conformity, and aligning Islamic values with modern technologies. Contemplating the future trajectory, it juxtaposes scientific advancements with philosophical reflections, acknowledging challenges posed by conflicting secular liberal ideologies. The text highlights social media and educational initiatives' pivotal roles in nurturing close-knit Muslim community relationships. In conclusion, it underscores the necessity of managing cognitive schemas and mitigating extreme psychological reactance in Islamic societies, advocating for a harmonious blend of punitive measures and core Islamic values, contributing significantly to the discourse on contemporary Islamisation